2007
DOI: 10.2116/analsci.23.59
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Glucose Sensor Prepared by Electropolymerization of Pyrroles Containing a Tris-bipyridine Osmium Complex

Abstract: A glucose sensor was developed by electrocopolymerization using pyrroles containing a tris-bipyridine (bpy) osmium complex (Os-py), pyrrole (py), pyrrole propanoic acid (PPA) and glucose oxidase (GOx) to improve the key performance characteristics, such as the sensitivity, selectivity, and long-term stability. Tris-bipyridine osmium pyrrole complexes with four different methylene moieties were utilized to correlate the methylene length with the glucose sensor performance. The electrocatalytic response of gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Similar phenomena were observed on a GOx immobilized electrode prepared by the electropolymerization of pyrrole derivatives containing a gluconyl-and osmium bipyridine complex with a methylene-terminal group introduced at the 1-position. 25,26 A constant potential of 1.20 V (vs. Ag/AgCl) was applied for the electropolymerization of all pyrrole derivatives. After a deposition charge of 7 mC mm -2 was passed, black thick films were obtained on the surface of the electrode for 5a, 5b and 5c, while 5d provided only colorless thin film.…”
Section: Electrochemical Behavior Of Pyrrole Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar phenomena were observed on a GOx immobilized electrode prepared by the electropolymerization of pyrrole derivatives containing a gluconyl-and osmium bipyridine complex with a methylene-terminal group introduced at the 1-position. 25,26 A constant potential of 1.20 V (vs. Ag/AgCl) was applied for the electropolymerization of all pyrrole derivatives. After a deposition charge of 7 mC mm -2 was passed, black thick films were obtained on the surface of the electrode for 5a, 5b and 5c, while 5d provided only colorless thin film.…”
Section: Electrochemical Behavior Of Pyrrole Derivativesmentioning
confidence: 99%
“…There is a growing interest in using electrochemically generated polymers, such as polypyrroles, in biosensor applications primarily as immobilization matrices because such allows the precise localization of enzymes and hence is ideal for enzyme deposition at miniature electrodes. [16][17][18][19][20][21][22][23][24][25][26] It seemed attractive to prepare N-substituted pyrrole polymers containing phosphatidylcholine, since the obtained electrogenerated film can be prospected to act as a hemocompatible material. The authors have reported that such pyrroles are useful for the immobilization of glucose oxidase (GOx) on platinum electrode and the obtained GOx-immobilized electrode functioned as a glucose sensor with good long-term stability.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] With respect to the practical use of enzyme sensors and biofuel cells one of the most important factors is the stable immobilization of all components related to the electron transfer process, from the substrates to the electrode. [15][16][17][18][22][23][24] The electrodes with components modified for electrochemical detection of an enzyme reaction are generally called reagentless electrodes; they work by the addition of only the substrates. In fact, Smolander et al reported a PQQ-aldose dehydrogenase modified carbon paste (CP) electrode for flow-injection analysis of aldose sugars.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of osmium derivatives have been successfully used as electron transfer mediators for glucose biosensor fabrications [15, 16, 19 -23]. The electron transfer mediator can be immobilized on the electrode surface by different methods such as, adsorption [24], self-assembled monolayers [25], simply mixing into carbon paste [26] direct electropolymerization [27] entrapped into conductive polymer [28] covalent attachment [29] and sol-gel techniques [30]. Unfortunately, more of the modified electrodes based on osmium derivatives have certain disadvantageous, such as considerable leaching of electron transfer mediators and poor long term stability.…”
Section: Introductionmentioning
confidence: 99%